育仔放棄されたネズミイルカの初乳の成分分析と人工哺育の試み - MATSUSHIRO, Marin; 22077; TSUNOKAWA, Masatoshi; 22078; MATSUISHI, Takashi; 22079; 郡山, 尚紀; 9783; 9409 (Japanese Journal of Zoo and Wildlife Medicine, 2020)
Article The harbor porpoise is a marine mammal rarely seen in aquariums. The ecology of this species is not well known, and captive breeding is difficult without essential information such as milk composition, amount consumed and frequency nursed per day, and lactation period. At the Otaru Aquarium in Japan, several deliveries of harbor porpoise offspring have occurred, but the calves have not survived. In the present study, we analyzed the colostrum of a harbor porpoise and attempted to hand-rear a calf using artificial milk after the mother denied nursing. The crude fat and crude protein contents of the colostrum were relatively high compared to values for other odontocetes. The present information will be helpful for future efforts to hand-rear harbor porpoises. 本研究では，おたる水族館で育仔放棄されたネズミイルカ幼獣の人工哺育を試みた。生後14日で幼獣は死亡したが，母獣から貴重な初乳を得た。ハクジラ類の中でも本種は授乳期間が短いが，成分分析の結果，その初乳には粗脂肪と粗蛋白質が豊富に含まれていた。 journal article